Implementasi Peraturan DPRD Provinsi Banten Nomor 1 Tahun 2020 Tentang Tata Tertib pada Badan Pembentukan Peraturan Daerah DPRD - Andra Soni; Suwaib Amirudin; Ipah Ema Jumiati (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
There is still a draft local regulation that has been set in the Banten Province regional formation program (propemperda) but at the end of the year it is not entirely discussed by the governor and the Banten Provincial DPRD, researchers need to conduct further research on how bapemperda in harmonizing, rounding, and stabilizing the conception of the draft local regulation so that it is determined to be a propemperda. This research method uses descriptive qualitative research methods and data collection techniques using observation and documentation studies. The results showed that policy implementation according to O. Jones showed that the Bapemperda organization still did not all have a legal background, the Bapemperda expert group/team had not been given training in supporting Bapemperda's performance and communication between the commission and Bapemperda was still weak. The finding of this research is that there is still a need for awareness from the elements of DPRD leaders and leaders of DPRD Organs.